Relevance of the prioritized curriculum with emphasis on competencies: teachers' perspectives on the teaching of mathematics in Bachelor of Science - Lima-Yarpaz, Jhon (2025)
This article analyzes the relevance of implementing the prioritized curriculum in the teaching and learning of mathematics among second-year science baccalaureate students during the 2023-2024 academic year. This article focuses on the development of communication, mathematical, digital, and socioemotional competencies, as defined by the Ministry of Education. This research, based on teachers' perceptions of their classes and their use of the mathematics textbook provided to students, focuses on qualitative and quantitative approaches. The research combines documentary analysis with a field study, conducting surveys with teachers from 22 educational institutions in Quito. A worksheet was used for text analysis. The results show a high level of contextualization and relevance in the implementation of the curriculum, as well as a significant promotion of mathematical and socioemotional competencies. However, the development of digital competencies shows a medium level of integration. Regarding the text analysis, it was determined that the limit of a function is not studied. It is concluded that, although there is an effort to incorporate these competencies into the teaching-learning process, it is necessary to strengthen training in the use of digital tools and improve textbooks to ensure more effective implementation of the prioritized curriculum.